2006
DOI: 10.1097/01.ta.0000208126.22089.b6
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Coated Dressing Acticoat Caused Raised Liver Enzymes and Argyria-like Symptoms in Burn Patient

Abstract: This is the first report on silver toxicity in a patient with 30% burns who received Acticoat for local treatment. Due to substantial experiences with adverse SSD reactions and side effects, it is appropriate to keep the possibility of a toxic silver effect in burn patients treated with Acticoat silver-coated wound dressing in mind. The silver levels in plasma and/or urine should be monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
198
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(214 citation statements)
references
References 22 publications
4
198
0
12
Order By: Relevance
“…Furthermore, increased liver enzymes were reported in Sprague-Dawley rats after Twenty-eight-day oral exposure to nano-silver particles (60 nm) . It was reported that silver-coated dressing acticoat caused raised liver enzymes and argyria-like symptoms in burn patients (Trop et al 2006). The in vitro and in vivo studies revealed toxicity effects of silver nanoparticles on immune system, especially cytokine excretion.…”
Section: Toxicity Of Nano-silver Particlesmentioning
confidence: 99%
“…Furthermore, increased liver enzymes were reported in Sprague-Dawley rats after Twenty-eight-day oral exposure to nano-silver particles (60 nm) . It was reported that silver-coated dressing acticoat caused raised liver enzymes and argyria-like symptoms in burn patients (Trop et al 2006). The in vitro and in vivo studies revealed toxicity effects of silver nanoparticles on immune system, especially cytokine excretion.…”
Section: Toxicity Of Nano-silver Particlesmentioning
confidence: 99%
“…However, very recently Verano-Braga et al (2014) reported that the toxicity of AgNPs depends upon both dosage and particle size. Metal nanoparticles show large surface to volume ratio and exhibit antimicrobial properties due to their ability to interact with cellular membranes through disruption of cell wall structure (Ahmad et al 2013;Trop et al 2006). Especially silver has long been known for its strong toxicity against a wide range of micro organisms including bacteria and fungi (Narayanan and Park 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far a single case report has been published that describes a case of argyria occurring in a patient with 30% burns treated with a silver-coated wound dressing. 31 Our patient's leukopenia was attributed to the elevated silver levels resulting from the use of the silverimpregnated sponge. Initially it was thought that the patient might have a transient leukopenia from underlying sepsis and malignancy.…”
Section: Discussionmentioning
confidence: 99%